MR evaluation of frontal sinus osteoplastic flaps with autogenous fat grafts. - Loevner, L A; Yousem, D M; Lanza, D C; Kennedy, D W; Goldberg, A N (American Journal of Neuroradiology, 1995)
PURPOSE To investigate the MR findings in patients who have had osteoplastic frontal sinus flaps placed for inflammatory sinonasal disease. METHODS The MR images of 13 patients who had improvement of symptoms after osteoplastic frontal sinus flap placement with fat autograft were prospectively evaluated for the presence of high intensity on T2-weighted scans, contrast enhancement, and replacement of frontal sinus fat by lower-signal soft tissue. All studies were performed on a 1.5-T unit using a 5-in round surface coil placed over the nasion. Sagittal T1-weighted, axial and coronal fast spin-echo T2-weighted, and precontrast and postcontrast axial and coronal T1-weighted images were obtained through the operative bed. The T2-weighted and postgadolinium sequences were done with a fat-suppression technique. RESULTS Hyperintensity within the frontal sinuses on T2-weighted images and enhancement (peripherally and/or centrally where fat was replaced with soft tissue) were found to some degree in all patients. The degree of replacement of frontal sinus fat with soft tissue ranged from 4% to 85% (mean, 43%). Five patients with persistent symptoms had no distinguishing MR features when compared with asymptomatic patients. CONCLUSIONS Although increased T2-weighted intensity, fat replacement, and enhancement are findings compatible with inflammation, these changes may be seen in patients who are asymptomatic after placement of osteoplastic frontal sinus flaps; they may represent the normal granulation process. MR findings after flap placement are nonspecific and have limited utility in distinguishing symptomatic patients with recurrent inflammatory disease from asymptomatic patients whose imaging findings are related to postoperative scar tissue.